Effects of creatine monohydrate supplementation on simulated soccer performance - Williams, J.; Abt, G.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To determine the effects of acute short-term creatine (Cr) supplementation on physical performance during a 90-min soccer-specific performance test. Methods: A double-blind, placebo-controlled experimental design was adopted during which 16 male amateur soccer players were required to consume 20 g/d Cr for 7 d or a placebo. A Ball-Sport Endurance and Speed Test (BEAST) comprising measures of aerobic (circuit time), speed (12- and 20-m sprint), and explosive-power (vertical jump) abilities performed over 90 min was performed presupplementation and postsupplementation. Results: Performance measures during the BEAST deteriorated during the second half relative to the first for both Cr (1.2-2.3%) and placebo (1.0-2.2%) groups, indicating a fatigue effect associated with the BEAST. However, no significant differences existed between groups, suggesting that Cr had no performance-enhancing effect or ability to offset fatigue. When effect sizes were considered, some measures (12-m sprint, -0.53 ± 0.69; 20-m sprint, -0.39 ± 0.59) showed a negative tendency, indicating chances of harm were greater than chances of benefit. Conclusions: Acute short-term Cr supplementation has no beneficial effect on physical measures obtained during a 90-min soccer-simulation test, thus bringing into question its potential as an effective ergogenic aid for soccer players.